Sleeping beauty and other stories - Moo-Young, Ian; Andersen, Hans Christian; Grimm, Brothers ([S.l.] : Moo Movies [production company] ; [S.l.] : Longman ELT Video [distributor], 1982)
This fairy tales contains four stories for young learners of English
This videocassette features the four titles: Sleeping beauty, Little red riding hood, Goldilocks and the three bears, Rumpelstiltskin
Editor, Tony Fish, Peter Hearn
Storytellers: John Newton, Anne Rosenfeld
Keywords: Fairy tales; Children's stories, English; Fairy tales -- Film and video adaptations